Optical Properties of SnS2 Thin films Prepared By Chemical Spray Pyrolysis - Hussain, N. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films of tin disulphide SnS2 with different thicknesses (2500,4000,5000)A0 have been prepared by chemical spray pyrolises technique on substrate of glass with temperature (603)K . The effect of thickness on the optical properties of SnS2 has been studied.the optical study that includes the absorptance and transmittance spectra in the wavelength range (300900)nm demonstrated that the value of absorption coefficient (Î±) ) was greater than (104 cm-1) the electronic transitions at the fundamental absorption edge were of the indirect kind whether allowed and forbidden . Absorption edge shift slightly towards higher wave length.The value of energy gaps (Eg) for all the films prepared are decreased with increasing the thickness. Absorption and transmission spectra were used to find the optical constant including refractive index(n), extinction coefficient (k), imagenary and real part of dielectric constant (Â£i , Â£r), and it was found that all the optical constant was affected .